The effect of CAR, NPF, BOPO and FDR on the profitability of Sharia Commercial Banks registered in the financial services authority for the 2016-2020 period - Nurdahlia Nurdahlia; Kasmawati Kasmawati; Rani Munika (STIE Bangkinang Publishing, 2022)
While the purpose of this study is to determine the effect of Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), BOPO and Financing to Deposit Ratio (FDR) on Islamic Commercial Banks registered with OJK. Based on the results of hypothesis testing, it is surprising that U F (simultaneous) variables Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), BOPO and Financing to Deposit Ratio (FDR) have an effect on Profitability of Islamic Commercial Banks. And the results of the study partially only Capital Adequacy Ratio (CAR) and BOPO that affect Profitability Hose Non Performing Financing (NPF) and Financing to Deposit Ratio (FDR) have no effect on Profitability. The magnitude of the effect is 61.4 percent.